(untitled) (Research, Society and Development, 2024)
Sports injuries, especially those involving the anterior cruciate ligament (ACL), are common among athletes and can significantly impair knee functionality and the quality of life of affected individuals. This study aims to review advanced surgical treatments for ACL reconstruction, exploring different techniques and their implications for recovery and return to sports activities. The methodology involves a narrative literature review using databases such as PubMed, Google Scholar, and SciELO, analyzing articles on procedures such as autografts, arthroscopic techniques, and combined ligament reconstruction methods. The results show that various techniques are widely used for ACL reconstruction, with significant differences in functional recovery and postoperative pain management. Furthermore, advances such as the use of thicker grafts and minimally invasive techniques have been shown to improve knee stability and reduce rupture rates. New therapies, including biomaterials and grafts combined with growth factors, are under investigation to enhance graft integration and healing. ACL injuries remain a significant challenge in sports, requiring personalized surgical approaches to ensure satisfactory functional outcomes. The combination of traditional techniques and biomedical innovations offers considerable potential for improving patient prognosis, but additional studies are needed to evaluate the long-term effectiveness of these interventions.